DIGITAL MARKETING STRATEGY RESEARCH ON SPORT BRANDS: CASE OF LINING AND XTEP, CHINA - Hao Xiang; Tubagus Achmad Darodjat (International Journal of Innovations in Engineering Research and Technology, 2021)
The purpose of this project is to determine the impact of digital marketing on Chinese sports brands through a case study of the integration and comparison of two Chinese sports brands-Lining and Xtep. Provide reference for these two brands to better use digital marketing. This is mainly by showing the digital marketing platforms/channels of these two brands and discussing the impact (positive/negative) of this kind of digital marketing on these two brands, in order to fill the gaps in the previous research on the integrated use of Chinese sportswear brands; in addition, This research further defines the challenges/obstacles that these two brands face when using digital marketing, and how they respond to these challenges and make better use of digital marketing based on consumers.